Valorization of cultured macroalgae using lipid signatures - Lopes, Diana Carla Salzedas (2023)
The production and consumption of marine macroalgae, or seaweeds, are well established in southeastern Asian countries. At present, the global perception of macroalgae as a “superfood” with beneficial properties is leading to an increase in their demand and consumption in Western countries in the Northern Hemisphere. This new trend is boosting the commercialization of marine macroalgae in the European Union. However, as the offer of macroalgae in Europe still mostly relies on the harvesting of biomass from wild stocks, their production in aquaculture is slowly emerging to ensure a safer and higher quality offer. Currently, the incentive of the European Green Deal and recommendations for the consumption of macroalgae in sustainable and healthy diets are expected to further increase their production, market, and consumer’s engagement. Marine macroalgae represent a source of essential nutrients being recognized as nutraceuticals with beneficial effects on health and nutrition, highlighting their role in the prevention of Non-Communicable Diseases (NCD), which include obesity, diabetes, cardiovascular diseases, and hypertension, among others. The dietary benefits of marine macroalgae are not restricted to their essential nutrients, but also to the occurrence of other bioactive phytochemicals. Despite their low content, lipids of marine macroalgae represent a valuable source of molecules carrier of essential polyunsaturated fatty acids (PUFA) with high nutritional value. Moreover, complex lipids, also identified as polar lipids, of macroalgae have recently started to receive a renewed attention due to their biological activity, health promoting benefits, and contribution to the prevention of NCD. The lack of knowledge on the lipidome of marine macroalgae, as well as their bioactive properties, still impairs researchers to unlock their full biotechnological potential. The main objectives of this Thesis were to perform the identification of the lipidome of edible and commercialized marine macroalgae using state-of-theart lipidomic approaches, based on mass spectrometry analysis coupled to chromatographic methods; to develop a molecular tool based on lipid signatures for valorization and traceability, and evaluate the bioactivity of their lipid extracts. All marine macroalgae studied in the present work were produced in a landbased integrated multitrophic aquaculture (IMTA) system and the following species were addressed: Ulva rigida and Codium tomentosum from phylum Chlorophyta (green macroalgae); Palmaria palmata, Gracilaria gracilis and Porphyra dioica from phylum Rhodophyta (red macroalgae); and Fucus vesiculosus from phylum Ochrophyta (brown macroalgae). The lipidomic profile of macroalgae was identified using liquid chromatography – high resolution mass spectrometry (LC-MS) and gas chromatography - mass spectrometry (GC-MS). Lipid quality indexes, antioxidant, anti-inflammatory, and antiproliferative activities of their polar lipid extracts were also investigated. To gain a more in depth knowledge on the bioactive potential of lipids from marine macroalgae, a systematic review of the literature was performed, and it was found that the majority of studies available to date evaluate the activity of organic extracts, with only a few isolating and performing a molecular characterization of bioactive compounds. The few studies currently published highlighted the antiproliferative and anti-inflammatory activities of marine macroalgae glycolipids species, but much more research is still needed to unravel the putative biological activities of lipids from marine macroalgae. On evaluation of species-specific bioactivity, the polar lipid extracts of U. rigida displayed the lowest atherogenicity and thrombogenicity indices; the lipid extracts of P. palmata and F. vesiculosus displayed the highest antioxidant activities measured by DPPH● and ABTS●+ radical scavenging activities; the lipid extracts of U. rigida, C. tomentosum, P. palmata, and P. dioica featured a higher anti-inflammatory activity measured by inhibition of COX-2 activity, while those of P. dioica and P. palmata showed a better performance on their antiproliferative activity with highest cytotoxic potential in the MDA-MB-231 breast cancer cells. It is worth highlighting that while the bioactivities reported were restricted to the lipid extract, whose major components were polar lipids, the role of other lipid-soluble molecules (e.g., pigments) or any synergist effect between them cannot be excluded. A huge diversity of polar lipid species was unraveled in the marine macroalgae surveyed in the present work, with these biomolecules being mostly present as phospholipids, glycolipids, and betaine lipids. Furthermore, several of these lipids were esterified to PUFA with beneficial omega-3 fatty acids, such as alpha-linolenic acid (ALA), and docosapentaenoic acid (DPA) on U. rigida and eicosapentaenoic acid (EPA) on P. palmata. EPA content on P. palmata reached a relative abundance greater than 50%. To better understand the specificity of lipid signatures between different phyla and species, a comparison of the lipid profile displayed by the six macroalgae addressed revealed a total of 477 different polar lipids species, with only 35 being shared between all the species surveyed. The comparison of the lipidome also revealed that the distribution of polar lipid classes showed a trend by phylum (e.g., PI-Cer typical of red seaweeds and DGTA typical of brown seaweeds), although some insights of species specific at molecular level have been highlighted. In upcoming years, the production of marine macroalgae can make an important contribution to promote the blue bioeconomy. This work enhances the valorization of farmed macroalgae as promising ingredients for sustainable diets and their use for biotechnological applications.